The mysterious disappearance of Aidan S. (as told to his brother) - Levithan, David (Alfred A. Knopf, 2021)
"Aidan disappeared for six days. Six agonizing days of searches and police and questions and constant vigils. Then, just as suddenly as he vanished, Aidan reappears. Where has he been? The story he tells is simply. . . impossible. But it's the story Aidan is sticking to. His brother, Lucas, wants to believe him. But Lucas is aware of what other people, including their parents, are saying: that Aidan is making it all up to disguise the fact that he ran away. When the kids in school hear Aidan's story, they taunt him. But still Aidan clings to his story. And as he becomes more of an outcast, Lucas becomes more and more concerned. Being on Aidan's side would mean believing in the impossible. But how can you believe in the impossible when everything and everybody is telling you not to?"--Amazon.